Learners' Perception on Online Learning Implementation during Covid-19 Pandemic - Indry Widyasti Anwar; Jusmin HJ Wahid (Universitas Pendidikan Mandalika, 2021)
The massive and fast spread of the COVID 19 virus around the world has changed the way education works. The learning delivery in Schools and universities has been switched from conventional classrooms to online mode. This study aims to identify the learner's perception regarding online learning implementation during the COVID-19 pandemic. Participating in the study were 68 students of the English Education Study Program. Data collection was done through a survey questionnaire consisting of both open-ended and close-ended questions. Researchers presented the results using descriptive qualitative techniques. Results from this research showed that students have a positive attitude toward the online learning experience in general. The implementation of online learning during a pandemic is considered an effective and cheap way of accessing knowledge. However, most students showed frustration due to bad internet access, which affects their learning success. Students also felt the need for improvement in terms of interaction and engagement between students and teachers.